Three dimensional analysis of melting performance of phase change materials in a disk-shaped container with partial circular heating - Kiyak, Burak; Öztop, Hakan Fehmi; Aksoy, I. Gokhan (Taylor & Francis Inc, 2025)
Three dimensional analysis of melting performance of phase change materials in a disk-shaped container with partial circular heating has been studied. The phase change materials (PCMs) have succeeded in coming to the fore with their superior features in energy storage. However, the energy storage efficiency of these materials affected by many physical parameters, and determining the appropriate parameters is important for efficient energy storage. This study explores melting and energy storage performance of PCM-RT25 in a disk-shaped container with various partial circular heating cases and aspect ratios (AR). PCM melting analysis was performed with partial heating by selecting equal heating surface area on the disk. The effects of AR on melting performance were analyzed by observing the PCM melting behavior for different disk heights while keeping the disk diameter constant. Governing equations are solved by using finite volume method. Obtained results showed that the PCM melting time decreases as the AR increases in the case of full heating. In partial heating, the increase in AR not only extended the melting time, but also decreased the liquid fraction at the end of the melting. Parameters of AR = 4 and Delta T = 45 degrees C was provided the maximum liquid fraction in partial heating cases. Under these conditions, 90%, 94% and 96% liquid fractions were obtained at the end of melting for the cases that the heater is located in the center of the disk, in the middle near the inner part of the disk and in the middle near the outher part of the disk, respectively.
Keywords: Aspect ratio; disk-shaped container; energy storage; melting; partial heating; phase change material